Continuous interscalene catheters for ambulatory shoulder surgery provide effective intraoperative and early postoperative analgesia in adolescent patients. Issue 4 (16th June 2020) - Holland, Erica; Low, Daniel; Bompadre, Viviana; Saper, Michael
Abstract : Objectives: To review the analgesic efficacy (by means of pain scores and opioid consumption) and adverse events after interscalene catheter (ISC) placement for ambulatory shoulder surgery in a series of adolescent patients. Methods: A retrospective review was performed of 36 patients who underwent ISC placement. Intraoperative and postoperative data regarding block placement, opioid consumption and pain scores were recorded. Via telephone, patients were assessed on postoperative days (PODs) 1-3 for pain scores, oxycodone use, global satisfaction and adverse effects of treatment. Results: The mean age was 15.4±1.8 years. The average time of ISC placement was 11.8±3.8 min. The mean postanaesthesia care unit maximum pain score was 1.6±2.4 with four patients who received rescue intravenous morphine. Mean pain scores for POD 1- 3 at rest were 2.5±2.3, 2.1±1.5 and 1.8±1.6, respectively. Mean number of doses of oxycodone on POD 1–3 were 1.1±1.4, 1.5±1.8 and 0.7±1.3, respectively. Satisfaction was reported in 94% of patients and 97% would have the catheter again. Adverse events included two accidental catheter removals at the end of the procedure or in the recovery unit, one catheter replacement at the end of surgery due to dislodgement, two early catheter removals on POD 2 because of dressing failure and insertion site discomfort, three cases of Horner's Syndrome and one patient with transient ipsilateral facial numbness on POD 3. Conclusion: The use of ISCs in adolescent ambulatory shoulder surgery is beneficial, providing effective intraoperative and early postoperative analgesia as evidenced by low pain scores and minimal opioid use. Their routine use should be considered as they minimise perioperative opioid use with minimal adverse events. Level of evidence: Level IV, case series.